Pemanfaatan Facebook Ads Untuk meningkatkan Brand Awareness pada Produk Lokal - Aprinta, Gita (Universitas Semarang, 2016)
Facebook ads is the most recent feature ad in facebook. Its simply stated as paid advertisment to help products in increasing their brand awareness. The objective is to optimazing brands who want to reach thousands of costumers, by maximzing promotion through facebook ads. Brand awareness is quite important for costumer to help them recalling brand, doing the purchasing, and have loyal to specific brand. Facebook ads providing huge opportunity for each costumer to know, recall, involve and participate in sharing information to other social media users.